â€œNIRMANA-KOMPOSISI TAK BERBENTUKâ€ SEBAGAI DASAR KESENIRUPAAN FAKULTAS SENI RUPA INSTITUT KESENIAN JAKARTA - Ayu, Ardianti Permata (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2013)
’Nirmana-Formless Composition’ as a Basic of Fine Art FSR IKJ. Faculty of Fine Art, Jakarta Art Institute (FSR IKJ) is an institution in Indonesia which has important role in producing qualified artists and designers. To produce qualified works, students have to master the basic principles in fine art. One is through the lessons Nirmana as a’ formless composition’. The objectives of this article are (1) to discuss Nirmana, (2) to find out how it affects the primary education of fine art in Faculty of Fine Art IKJ (3) How the teaching pattern of Nirmana lesson that should be given to PDSR students in FSR IKJ so that they can explore their works which being created, have aesthetic values and be able to responsible The methods used in this article are study of literature and analyzed descriptively. The conclusions are: (1) Nirmala is the core which is very important and compulsory to be implemented in any art and design. The Nirmala is subject taught at FSR IKJ which includes the elements existed in any arts and design. (2) By mastering the Nirmala students are able to create and explore their works in arts and design properly and responsively (3) The Nirmala teaching pattern should be well-design and systematically given to the students followed by exercises.